2016
DOI: 10.1515/ract-2015-2566
|View full text |Cite
|
Sign up to set email alerts
|

Uses of alpha particles, especially in nuclear reaction studies and medical radionuclide production

Abstract: Alpha particles exhibit three important characteristics: scattering, ionisation and activation. This article briefly discusses those properties and outlines their major applications. Among others, -particles are used in elemental analysis, investigation and improvement of materials properties, nuclear reaction studies and medical radionuclide production. The latter two topics, dealing with activation of target materials, are treated in some detail in this paper. Measurements of excitation functions of -particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 217 publications
0
38
0
Order By: Relevance
“…All the three radionuclides constitute a high-spin isomeric state of the respective isotope. As discussed recently in detail [31], such states are preferentially populated in α-particle induced reactions. Some production data for the three radionuclides are available [cf.…”
Section: Novel Therapeutic Radionuclidesmentioning
confidence: 77%
“…All the three radionuclides constitute a high-spin isomeric state of the respective isotope. As discussed recently in detail [31], such states are preferentially populated in α-particle induced reactions. Some production data for the three radionuclides are available [cf.…”
Section: Novel Therapeutic Radionuclidesmentioning
confidence: 77%
“…A detailed discussion on the use of different charged‐particle–induced reactions over several energy ranges for the production of novel positron emitters is given in several references . We consider below 4 radionuclides, namely, 64 Cu, 86 Y, 124 I, and 73 Se.…”
Section: Novel Positron Emission Tomography Radionuclidesmentioning
confidence: 99%
“…The calculated thick target yields, however, showed that owing to the very short range of α particles, the (α,n) reaction is not very advantageous (cf Figure 2). From those yields and also considering the levels of the associated longer‐lived impurities 75 Se ( T ½ = 120.0 d) and 72 Se ( T ½ = 8.5 d), it was concluded that the 75 As(p,3n) 73 Se reaction over the energy range of E p = 40 → 30 MeV is most suited. The yield of 73 Se amounts to 1400 MBq/μA·h, and the levels of 75 Se and 72 Se impurities are 0.05% and 0.11%, respectively, of the amount of 73 Se.…”
Section: Novel Positron Emission Tomography Radionuclidesmentioning
confidence: 99%
“…Furthermore, the nuclear process nat Br(p,x) 73 Se was investigated, providing 73 Se with only minimal impurities . A critical analysis of the various competing reactions for the production of 73 Se was recently presented …”
Section: Selenium‐73mentioning
confidence: 99%